Relationships of Professional Nursing Practice Model-Modified Primary Nursing Method Implementation With Patient’s Satisfaction Level In Cendrawasih Ward at Wangaya Hospital Denpasar. - Sri Wulandari, Ni Nyoman (Coping: Community of Publishing in Nursing; Vol 1 No 2 (2013): JURNAL EDISI JULI-DESEMBER 2013, 2013)
One of the nursing profesionalisme effort is to improve nursing process quality, which can be evaluated through the implementation of nursing process, patient perception to nursing process, and patient satisfaction level. An alternative of quality improvement in providing nursing process is through application Professional Nursing Practice Model-Modified Primary Nursing Method in which nursing process is provided comprehensively. This study was aimed to analyze the relationships of professional nursing practice model-modified primary nursing method implementation with patient’s satisfaction level in Cendrawasih Ward at Wangaya Hospital Denpasar. This study includes the type of assosiatif/correlation study using cross sectional design. Sample consisted of 56 patients in Cendrawasih Ward at Wangaya Hospital Denpasar. The data was collected by providing questionnaires to the patients and nurses. The results obtained with the test of Rank Spearman correlation p value (0.000) < ? value (0.05) and compute r=0.724 is in the interval of 0.600-0.799 which means there is a strong significant relationship between the professional nursing practice model-modified primary nursing method implementation with patient’s satisfaction level in Cendrawasih Ward at Wangaya Hospital Denpasar
Keywords: modified primary nursing method, professional nursing practice model implementation, patient’s satisfaction